2013
DOI: 10.5267/j.msl.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Ranking critical success factor in chaos management using BSC and AHP method

Abstract: Managing an organization under chaos and uncertainty is often a concern of academic society. These days, we may face unpleasant natural, economical or even political incidents where mangers need to handle them, properly. This paper presents an empirical survey to investigate on an electromotor maker when it faces different chaos. The proposed study uses balanced scorecard in terms of four different perspectives including internal process, learning and growth, customer and financial performances. For each persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…Langkah-langkah yang harus dilakukan dalam menentukan prioritas kriteria adalah: memasukkan nilai perbandingan tingkat kepentingan kriteria berdasarkan penilaian yang dilakukan oleh 3 orang responden yang mewakili tim penilai lomba kinerja kelurahan. Adapun matrik hasil perbandingan berpasangan berdasarkan kriteria [13], [14], [15] dapat dilihat pada table 3…”
Section: Menentukan Prioritas Kriteriaunclassified
See 1 more Smart Citation
“…Langkah-langkah yang harus dilakukan dalam menentukan prioritas kriteria adalah: memasukkan nilai perbandingan tingkat kepentingan kriteria berdasarkan penilaian yang dilakukan oleh 3 orang responden yang mewakili tim penilai lomba kinerja kelurahan. Adapun matrik hasil perbandingan berpasangan berdasarkan kriteria [13], [14], [15] dapat dilihat pada table 3…”
Section: Menentukan Prioritas Kriteriaunclassified
“…Penentuan prioritas alternatif dilakukan dengan cara yang sama seperti menentukan prioritas kriteria [13], [14], [15]. Susunan matrik alternatif berpasangan berdasarkan kriteria penguasaan materi , dapat dilihat pada Tabel 4.…”
Section: Menentukan Prioritas Alternatifunclassified
“…The results of their study indicated that the firm could reach 41.4% of its financial objectives, 87.38% of its customers' requirements, 66.13% of internal processes and 70.94% of its learning necessities according to four major BSC requirements. Khosravi et al (2013) used BSC for performance measurement based on four different perspectives including internal process, learning and growth, customer and financial performances. For each perspective, the proposed study used analytical hierarchy process to rank various sub-criteria.…”
Section: Introductionmentioning
confidence: 99%